Knowledge and attitude of insecticide treated nets use in malaria prevention and its associated factors among pregnant women in Umuahia North, Nigeria - Opara, Monica Onyinyechi; Muhamad Saliluddin, Suhainizam; Ismail, Suriani (Community Health Society Malaysia, 2017)
Introduction: The use of insecticide treated nets among pregnant women is of public health significance to protect the pregnant women and their babies. This study is aimed at determining the knowledge and attitude of insecticide treated nets use in malaria prevention and its associated factors among pregnant women. Materials and Methods: This was a cross-sectional study. 426 of pregnant women were selected from two hospitals in Umuahia North LGA. A validated questionnaire was administered to pregnant women. The main outcome measures were factors associated with insecticide treated nets use and predictors. Results: 90.7% had high knowledge on bed nets use while 51.9% had positive attitude towards the use of ITNs. Predictors of knowledge and attitude were determined using logistic regression analysis and results from Chi-square tests with p ≤ 0.25 were included. Conclusion: This study has identified that there is high level of knowledge, negative attitude among pregnant women in Umuahia North LGA, Abia State. However, predictors of knowledge and attitude were also determined.